Multi-Approach Analysis Reveals Local Adaptation in a Widespread Forest Tree of Reunion Island. (30th December 2020) - Garot, Edith; Dussert, Stephane; Domergue, Frdric; Jot, Thierry; Fock-Bastide, Isabelle; Combes, Marie-Christine; Lashermes, Philippe
Abstract: Detecting processes of local adaptation in forest trees and identifying environmental selective drivers are of primary importance for forest management and conservation. Transplant experiments, functional genomics and population genomics are complementary tools to efficiently characterize heritable phenotypic traits and to decipher the genetic bases of adaptive traits. Using an integrative approach combining phenotypic assessment in common garden, transcriptomics and landscape genomics, we investigated leaf adaptive traits in Coffea mauritiana, a forest tree endemic to Reunion Island. Eight populations of C. mauritiana originating from sites with contrasted environmental conditions were sampled in common garden to assess several leaf morphological traits, to analyze the leaf transcriptome and leaf cuticular wax composition. The relative alkane content of cuticular waxes was significantly correlated with major climatic gradients, paving the way for further transcriptome-based analyses. The expression pattern of cuticle biosynthetic genes was consistent with a modulation of alkane accumulation across the population studied, supporting the hypothesis that the composition of cuticular wax is involved in the local adaptation of C. mauritiana . Association tests in landscape genomics performed using RNA-seq-derived single-nucleotide polymorphisms revealed that genes associated with cell wall remodeling also likely play an adaptive role. By combining these different approaches, this study efficiently identified local adaptation processes in a non-model species. Our results provide the first evidence for local adaptation in trees endemic to Reunion Island and highlight the importance of cuticle composition for the adaptation of trees to the high evaporative demand in warm climates.